If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2y^3y+1=-3
We move all terms to the left:
2y^3y+1-(-3)=0
We do not support eypression: y^3y
| 3n-10=10 | | 4=x+6+4 | | -20=16x+4-4x | | 0.28x=13.44 | | (X)=1.5x+600 | | 4(2x+3)=2(4-5×) | | c2+ 9=12 | | 6a=a+30 | | c/29=12 | | 5x+6=15x | | 3/5x-9=2/9 | | p+19=2p | | 13.48-0.14x=12.91+0.06x | | X-7=-3+x | | 50=2b-10 | | 15x-3(2x-3)=8x+8 | | 0.04x^2=10 | | 9/5x=1/7 | | |12x+4|=16 | | u+72=9u | | x+8x-10=17 | | 26=2x+2 | | 9a=a+32 | | 3a-4/2=5-4a | | 8x+32=5+7x+21 | | 8x+4=-20= | | 19j-17=-17+19j | | -10p-10=7p+7 | | 6x/10=9 | | 12.91+0.06x=13.48+0.14x | | 3x+30-x=2x+30 | | -5(b+6)=-25-6b |